A novel “Integrated Biomarker Response” calculation based on reference deviation concept - Sanchez, Wilfried; Burgeot, Thierry; Porcher, Jean-Marc (Environmental science and pollution research international, 2013)
Multi-biomarker approaches are used to assess ecosystem health and identify impacts of environmental stress on organisms. However, exploration of large datasets by environmental managers represents a major challenge for regulatory application of this tool. Several integrative tools were developed to summarize biomarker responses. The aim of the present paper is to update calculation of the “Integrated Biological Response” (IBR) described by Beliaeff and Burgeot (Environ Toxicol Chem 21:1316–1322, 2002 ) to avoid weaknesses of this integrative tool. In the present paper, a novel index named “Integrated Biological Responses version 2” based on the reference deviation concept is presented. It allows a clear discrimination of sampling sites as for the IBR, but several differences are observed for contaminated sites according to up- and downregulation of biomarker responses. This novel tool could be used to integrate multi-biomarker responses not only in large-scale monitoring but also in upstream/downstream investigations.